A hybrid incentive-based peer selection scheme for unstructured peer-to-peer media streaming systems - Romero, Victor M. II (College of Engineering, University of the Philippines Diliman, 2015)
Incentive mechanisms are an essential component of peer-to-peer systems as they promote cooperation among peers motivated by the collective preference of the system towards active participants. The temporal nature of media streaming, however, make the problem of designing appropriate incentives more challenging. To account for the continuous nature of the streamed content, it is essential to implement a small buffer which aims to pull a contiguous set of chunks that are temporally close to the current chunk in playback. While the added constraint on a peer's window of interest helps realize a less interrupted stream, it maps peers in various playback positions which easily inhibits peer contribution despite willingness as a result of the lack of mutual interest. We propose a hybrid incentive scheme for mesh-based peer-to-peer streaming which utilizes the global contribution information of peers in conjuction to pairwise reciprocity derived from local exhcnage information to address the dual cases wherein mutual benefits can and cannot be expected. Through simulation, we show that our proposed approach effectively induces service differentiation in the system such that participants that are more active in the data diffusion process are awarded with superior streaming performance. Furthermore, even when available resource in the network is globally scarce as a result of free riding activity, the contributing peers are able to preserve their relative streaming performance.